Quantitative Colocalization Analysis of Multicolor Confocal Immunofluorescence Microscopy Images: Pushing Pixels to Explore Biological Phenomena - Zinchuk, Vadim (Japan Society of Histochemistry and Cytochemistry, 2007)
Quantitative colocalization analysis is an advanced digital imaging tool to examine antigens of interest in immunofluorescence images obtained using confocal microscopes. It employs specialized algorithms to estimate the degree of overlap of fluorescence signals and thus enables acquiring important new information not otherwise obtainable using qualitative approaches alone. As raw confocal images have high levels of background, they should be prepared to become suitable for reliable calculation of colocalization coefficients by correcting it. We provide concise theoretical basis of quantitative colocalization analysis, discuss its limitations, and describe proper use of the technique. The use of quantitative colocalization analysis is demonstrated by studying bile salt export pump and multidrug resistance associated protein 2 in the liver and major basic protein and platelet activating factor receptor antigens in conjunctiva. The review is focused on the applicability and correct interpretation of the results of colocalization coefficients calculations.